Some scientific publications of BPKIHS: a bibliometric study of articles listed in the Web of Science (Health Renaissance, 2012)
Scientific productivity of any academic institution is expressed by the total number of publications generated by its academic faculties and the use of the publication by scientific community. Citation analysis is done to evaluate the use of the publications. Use of the publication can be studied with the help of bibliometric analysis. Counting publication, publications trends, authorship patterns and citation analysis are parts of bibliometric analysis. Web of Science is one of the best databases which allow the study in the use of the publications through citation analysis. In this article, scientific articles produced by the faculties and other international affiliated faculties of BP Koirala Institute of Health Sciences have been studied. Citation analysis of scientific publications of BP Koirala Institute of Health Sciences is done with the help of the Web of Science, a product of Thomason Reuters.DOI: http://dx.doi.org/10.3126/hren.v10i2.6584 Health Renaissance 2012; Vol 10 (No.2); 139-143